Lorenz Dominance and Welfare: Changes in the U.S. Distribution of Income, 1967-1986 - Bishop, John A.; Formby, John P.; Smith, W. James (The Review of Economics and Statistics, 1991)
John A. Bishop, John P. Formby, W. James Smith, Lorenz Dominance and Welfare: Changes in the U.S. Distribution of Income, 1967-1986, The Review of Economics and Statistics, Vol. 73, No. 1 (Feb., 1991), pp. 134-139